Tingkat Perkembangan Wilayah Kabupaten Dan Kota Di Pulau Jawa - Wardana, Abila Krisna; Muta'ali, Lutfi (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Java Island has experienced rapid development in Indonesia, with a dense population and a crucial role in the trade, industry, services, culture sectors, as well as being the nation's food basket. Its economic growth has been driven by high urbanization in recent decades, creating new growth centers and increasing the demand for infrastructure. However, urbanization also presents challenges such as the emergence of megaregions, urban bias, and regional disparities. This study aims to determine the development level of regencies/cities in Java Island and the spatial patterns of their development. The method used is quantitative descriptive analysis with scaling techniques, Moran's I, and LISA. The dimensions used include economy, social, infrastructure and services, environmental, and ICT, consisting of 15 variables. The results show that in 2022, 31 regencies/cities on Java Island were classified as having a high level of development, 36 at a moderate level, and 52 at a low level. The regional development index on Java Island shows variations, where the economic and social dimensions are dominated by large cities such as Jakarta and Surabaya, while regions with lower indexes are spread across East Java. The infrastructure and services, as well as the ICT dimensions, show significant disparities, with areas like the Thousand Islands excelling in infrastructure access, while Lebak Regency and Cimahi City face limitations. Most regencies/cities are still at a low level of regional development, requiring interventions to improve infrastructure, the economy, and the quality of life to achieve more equitable development. The emerging spatial patterns show clustering or positive autocorrelation around metropolitan areas. There is a need for equity strategies to reduce disparities between regions, especially those far from metropolitan or megaregion areas.